Evaluasi Kapabilitas Industri Fotovoltaik Nasional Berbasis Kontribusi Teknologi - Atikah, Nurul; Harahap, Fatimah Insani; Hayati, Titi (Public Health and Safety International Journal, 2025)
Mapping the technological capabilities of the photovoltaic (PV) industry and its supporting sectors in Indonesia to optimize the utilization of solar energy whose potential reaches 207.8 GWp, while the utilization target is only 0.87 GW by 2025. The purpose of this study is to analyze the level of technological readiness through a Technometric model that focuses on the components of technoware (T), humanware (H), and infoware (I). Using a quantitative survey methodology with a sample of solar panel, cable, and mounting companies, this study measured the Technology Contribution Coefficient (TCC) as a hypothesis to assess industry capability. The main results show that the solar panel and structure industries have “excellent” capabilities with TCCs of 0.7204 and 0.7297, respectively, driven by strong H and I contributions. In contrast, cable companies are categorized as “good” with a TCC of 0.5651, indicating the need for improvement in the technoware component. In conclusion, it is recommended to prioritize technoware development through product design computing, humanware improvement through innovation training, and infoware strengthening through information dissemination. The results of this research are crucial for improving the competitiveness of the domestic PV industry and accelerating the achievement of the national energy mix target